Development of STEM-Based Virtual Reality to Enhance High School Students' Conceptual Understanding - Siti Sarah; Vandan Wiliyanti; Rahma Diani (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
The understanding of concepts among students is still relatively low due to the suboptimal use of learning media, making it difficult for students to grasp the material, especially abstract physics concepts. This research aims to develop STEM-based virtual reality media, as well as to determine its feasibility, user response, and effectiveness in improving high school students' conceptual understanding. The method used is research and development with the ADDIE model (analysis, design, development, implementation, evaluation), with the research subjects being 10th-grade students at SMAN 1 and SMAN 10 Bandar Lampung. The instruments used included validation sheets for media experts, materials, and test items; responses from students and educators; as well as concept understanding tests through pretests and posttests. The research results show that the developed media is deemed suitable based on the validator's assessment, with responses from educators and students indicating a very interesting category. The N-gain score with an average of g=0.55 indicates a moderate increase in students' conceptual understanding, making this media suitable and effective for use in learning.